Numerical simulation of high temperature effects on SOI mosfets - Goh, June Mei Hui. (2012)
This project is aimed to use Taurus workbench to perform process simulation and device simulation. In this project, MEDICI is used to perform device simulation under high temperature operation. Device parameters are obtained from the simulator to analyze the behavior under high temperature operation using MEDICI. Parameters obtained are analyzed using theoretical model.